2008
DOI: 10.1111/j.1095-8649.2007.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish mitochondrial genomics: sequence, inheritance and functional variation

Abstract: Mitochondrial genomic research currently primarily focuses on the analysis and understanding of how mitochondrial mutations produce detrimental phenotypes in humans. Reasons for this focus on negative impacts include the large number of human diseases that are known to result from specific mitochondrial genomes, and the long held belief that mitochondria change only through the accumulation of mutations due to its clonal, maternal inheritance. Recent studies are beginning to challenge these preconceptions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 129 publications
0
47
0
10
Order By: Relevance
“…Based on the shared biochemical pathways of intracellular energy production and the oxidation of carotenoids, Johnson and Hill (2013) recently suggested that carotenoid metabolism takes place at the inner mitochondrial membrane, highlighting the potential for functional sequence variation in the mitochondrial 85 genome (Lu et al 2010) to impact directly on coloration, much as it impacts aerobic performance (Harrison and Turrion-Gomez 2006;Niemi and Majamaa 2005). Given that mitochondria are maternally inherited (Brown 2008; though paternal leakage of mitochondrial DNA has been reported in birds: Kvist et al 2003), this raises the possibility that variation in carotenoid-based coloration is associated with extranuclear genetic variation. To our knowledge, this has not been 90 explored in natural populations, although the methodology for estimating mitochondrial contributions to phenotypic variation has been applied within the animal breeding literature (e.g., Garmyn et al 2011;Harrison and Turrion-Gomez 2006;Pritchard et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the shared biochemical pathways of intracellular energy production and the oxidation of carotenoids, Johnson and Hill (2013) recently suggested that carotenoid metabolism takes place at the inner mitochondrial membrane, highlighting the potential for functional sequence variation in the mitochondrial 85 genome (Lu et al 2010) to impact directly on coloration, much as it impacts aerobic performance (Harrison and Turrion-Gomez 2006;Niemi and Majamaa 2005). Given that mitochondria are maternally inherited (Brown 2008; though paternal leakage of mitochondrial DNA has been reported in birds: Kvist et al 2003), this raises the possibility that variation in carotenoid-based coloration is associated with extranuclear genetic variation. To our knowledge, this has not been 90 explored in natural populations, although the methodology for estimating mitochondrial contributions to phenotypic variation has been applied within the animal breeding literature (e.g., Garmyn et al 2011;Harrison and Turrion-Gomez 2006;Pritchard et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Because of differences in the mode of inheritance between mtDNA and the nuclear genome (Brown 2008), Yan et al (2008) recommended further research using nuclear DNA markers to verify their results. Against this background, we analyzed the genetic structure of bronze gudgeon using microsatellite DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…The two species clearly share a common evolutionary history, but given the nature of the marker used here (haploid, with strictly maternal inheritance) (Brown 2008), it may be necessary to consider alternatives explanations for the observed scenario.…”
Section: Demographic Historymentioning
confidence: 99%